The removal of zinc and plumbum (lead) by using hydrogen peroxide - Salimah, Shafii (2008)
Protection of ground-water and marine waters is a complex issue and a vital public concern. Once contaminated, it can be technically difficult and enormously expensive to clean up. One way to protect these waters from contamination is through the control of industrial discharges. Often though, control processes are not practical in treating high flow rates or those with relatively low contaminant concentrations. This proposal involves a process for removing heavy metals from wastewater streams using hydrogen peroxide. The specific contaminant addressed in this research are zinc and lead removal, which has become a serious concern because of its toxicity to human, animal and aquatic life. The main objective of this research is to study the effectiveness of hydrogen peroxide in the removal of heavy metal ions from wastewater. The scopes of this experiment are to determine the effect of hydrogen peroxide concentration and the effect of pH in order to get maximum removal heavy metal ions in wastewater. This experiment started by determining the concentration of hydrogen peroxide that has the maximum removal. Then the concentration of hydrogen peroxide is used to add to each five wastewater sample. Next, all samples were set to different pH which are 4, 6, 8, 10 and 12. At the end of this research, it was observed that the maximum removal of heavy metal was found to be at 30% v/v of hydrogen peroxide and at pH 8. The amount of lead and zinc reduced are 95.28% and 80.4%, respectively.